Literatur Review : Penggunaan Donor Sel Telur dalam Program IVF pada Wanita dengan Kegagalan Ovarium Prematur - Rani Wijayanti; Azniah Syam (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Premature ovarian failure (POF) is a condition where the ovaries stop functioning before the age of 40 years, resulting in permanent infertility. IVF with own eggs in POF patients has a very low success rate, so egg donation is the most effective alternative. This review aims to evaluate the effectiveness of using egg donors in IVF programs in women with POF, through an analysis of 20 studies systematically selected from international scientific databases. The results of the study showed that egg donation consistently increased the clinical pregnancy and live birth rates in POF patients, although accompanied by obstetric risks such as gestational hypertension and preeclampsia. New reproductive technologies such as in vitro maturation (IVM), stem cell therapy, and platelet-rich plasma (PRP) also provide additional prospects for restoring ovarian function. In conclusion, egg donation is a major strategy in the management of infertility due to POF, which requires the support of an integrated clinical, ethical, and policy approach.